Desain Mesin Pengolah Minyak Kelapa Secara Otomatis Kapasitas 20 Liter Per Jam - Sonong Sonong (Jurnal Teknik Mesin Sinergi, 2009)
Research into this which entitle design machine processor of palm oil automatically, aim to can yield the coconut mink of 20 litre each hour. Our research before all only can produce the mean of 10 coconut mink litre each hour. Whereas traditional machine which used by the society in this time only can produce the mean coconut mink of 5 coconut mink litre each hour. The society support with area potency as producer of coconut hibrida, and also request of market of palm oil, pushing to do this research designed the machine have of bigger capacities to be permeable of the labour more and profit society. Its is method, all component supporter of machine done by addition of volume and his strength through planning and calculation. Machine designed by the consist of: machine scar coconut flesh, and magle machine of is result of rasp, at the same time dissociate the result coconut mink with his dregs. Both the machine work automatically through activator motor. Rasp designed use the cylinder turn around the harsh jagged around surface of the cylinder which turned around use the electromotor. Magle machine designed use the plate stenless stell small holey which formed by be like mug which is on its underside is attached by the propeller knife, activator system the used is powered electromotor of low electrics. After done the testing at made machine and compared to the former machine and traditional machine, hence obtained by the result as follows: Former machine only can produce the mean of 10 coconut mink litre each hour, is while the machine design can produce the mean more than 20 coconut mink litre each hour meaning the storey of 50%. Traditional machine only can produce the mean of 5 coconut mink litre each hour mean experience of the improvement of 75% from the machine design.